1996
DOI: 10.1016/s1074-7613(00)80250-2
|View full text |Cite
|
Sign up to set email alerts
|

The Specificity and Orientation of a TCR to its Peptide–MHC Class II Ligands

Abstract: A T cell-mediated immune response is mainly determined by the 3-5 aa residues that protrude upwards from a peptide bound to an MHC molecule. Alterations of these peptide residues can diminish, eliminate or radically alter the signal that the T cell receives through its T cell receptor (TCR). We have used peptide immunizations of normal mice and mice carrying alpha or beta chain TCR transgenes to identify three distinct peptide contact points. One, near the carboxyl terminus of the peptide, involves the beta ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
103
1

Year Published

1997
1997
2004
2004

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(119 citation statements)
references
References 52 publications
15
103
1
Order By: Relevance
“…However, two of the APL were capable of antagonizing five out of the six hGAD65 (555-567)-responsive clones. These two APL have substitutions at the p5 position, a major contact site for TCR recognition of MHC-peptide [24][25][26]. The finding that no single APL was able to antagonize all six clones and that many were agonistic is similar to findings on MBP APL [27].…”
Section: 5supporting
confidence: 59%
“…However, two of the APL were capable of antagonizing five out of the six hGAD65 (555-567)-responsive clones. These two APL have substitutions at the p5 position, a major contact site for TCR recognition of MHC-peptide [24][25][26]. The finding that no single APL was able to antagonize all six clones and that many were agonistic is similar to findings on MBP APL [27].…”
Section: 5supporting
confidence: 59%
“…2B4 § -TG and 2B4 § -KI mice express the same TCR § chain with different regulatory elements [13,14], while 2B4 § -TG and D10 § -TG mice express different TCR § chains but use the same TCR transgenic expression vector [13,15]. All three mice express the transgenic § chain prematurely at the DN stage [13][14][15]. Analysis of their thymic cellularity and CD4/CD8 subset distribution showed that the total thymocyte numbers of the 2B4 § -KI, 2B4 § -TG, and D10 § -TG mice were less than˚20% that of B6 mice ( Fig.…”
Section: Decreased Dp Thymocyte Number In Tcr > -Transgenic Micementioning
confidence: 99%
“…Each of these regions forms a loop that point away from the T cell and contacts the antigen-HLA complex [8,9]. The CDR1 and CDR2, which are encoded within the V region genes, interact predominantly with the HLA molecule [10]. The CDR3 spans the junction of the V(D)J segments and interacts with the peptide antigen [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…The CDR1 and CDR2, which are encoded within the V region genes, interact predominantly with the HLA molecule [10]. The CDR3 spans the junction of the V(D)J segments and interacts with the peptide antigen [10,11]. The diversity of the CDR3 is generated by the mechanisms that join the V(D)J segments during the maturation of the T cell [12].…”
Section: Introductionmentioning
confidence: 99%